A Guide to the World Bank - World Bank (Washington, DC, 2013)
This book is intended for the wide range of people around the world who need basic information about the work of the Bank Group. This audience includes people working in all aspects of development, students, members of the general public, and staff members of the Bank Group itself. Because this audience is so broad, the text emphasizes the organizational and conceptual divisions of the Bank Group's activities and guides readers to potential sources of more-detailed explanations of the development work in progress. The annual reports of the Bank Group institutions provide more details on the volume and types of development assistance. The annual World Bank Group Directory lists telephone contacts for individuals and departments. The following chapters explain how the World Bank Group is organized; how it operates; and how its work focuses on countries, regions, and specific topics in development. Appendixes provide further information on Bank Group contacts, on the organization's history, on country membership and the voting shares in the institutions, on the sector and thematic categories for the Bank Group's activities, and on Bank Group resources in individual countries.